Implementation of ASUH Principles (Safe, Healthy, Wholesome, and Halal) in Qurban Animal Slaughtering at Sekolah Tinggi Maritim Yogyakarta - Adi Nugraha; Muhammad Jefriandi Astriawati; Rio Pebrian Indrata S. Si, M. Sc; Ningrum Astriawati; Benny Hartanto; Ardystia Maha Sari Maha Sari (Malik Al-Shalih : Jurnal Pengabdian Masyarakat, 2026)
The slaughtering of sacrificial animals (qurban) on university campuses is an annual activity that holds strategic potential for promoting Islamic jurisprudential education and public veterinary health. However, technical challenges are often encountered, particularly due to limited understanding among student committees and staff regarding animal welfare and hygienic meat handling. This community service activity aimed to assist in the implementation of qurban slaughtering at Sekolah Tinggi Maritim Yogyakarta in accordance with Islamic principles and the ASUH (Safe, Healthy, Wholesome, and Halal) standards, while minimizing environmental impacts. The activities included pre-qurban socialization, Halal Slaughterer (Juleha) training for students, ante-mortem and post-mortem examinations, and qurban waste management. The results demonstrated improved understanding among the organizing committee regarding humane animal handling techniques, effective slaughtering procedures, and the use of environmentally friendly meat containers, such as woven bamboo baskets (besek) and teak leaves, to reduce plastic waste. The findings also indicated that 100% of the sacrificial animals were fit for consumption and free from zoonotic diseases. Overall, the activity successfully established a model for campus-based qurban management that is compliant with Islamic principles, hygienic, and environmentally friendly.